Problem of Iddah khulu’ in Indonesia - Mustahal, Muhamad (Advances in Humanities and Contemporary Studies, 2024)
Majority of divorce cases in Indonesia are lawsuit divorce or Khulu’, where as majority of Indonesian women are working. This condition will impact or disturb the quality of their work if they need to wait for Iddah period to end. Iddah khulu’ that can be taken is considered light such as one time of woman’s period (menstruation) and basically it is similar to iddah ‘Talak’ (divorce filed by the husband). Iddah Khulu’ in Indonesia is similar to iddah Talak Bain, which 3 times of Women’s periods. This rule is based Holy Quran for general Iddah as mentioned on surah Al Baqarah 223. This rule/provision is also followed by Muslim scholar (Ulama) such as Imam Syafii. The other provision mention that Iddah khulu’ only consider one time Woman’s period which is based on Hadist ahad. While the theory Asy Sa]yafii on the interpretation of Hadith Ahad toward Holy Quran can be accepted. The purpose of this research is to analyze Hadith about Khulu’ and the impact or relation toward Indonesian peoples. The method used on this research is descriptive – quantitative where mostly based on library research, reading of literatures related to the subject of the research. The result of this research is the used of Hadith on Iddah Khulu’ which only mention one Woman’s period can be accepted and be used for consideration by respective authorities/bodies to change the law/rule of iddah khulu’s within KHI.